INTERAKSI BUDAYA ETIS DAN KECERDASAN SPIRITUAL PADA HUBUNGAN MUATAN ETIKA DAN PERILAKU ETIS MAHASISWA (Survey pada Pendidikan Vokasi Akuntansi di Yogyakarta) - Y, Rahmawati Hanny (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2017)
This study aims to analyze the interaction of ethical culture, spiritual intelligence, ethical content, and students' ethical behavior. The population in this study is a student at one of the leading accounting vocational education institutions in Yogyakarta. Sampling technique in this research use purposive sampling. The number of samples in this study was 368 respondents. Data analysis using Moderated Regression Analysis (MRA). The results of this study indicate that the content of ethics affect the student's ethical behavior. The interaction of ethical culture on the relationship between ethical content and ethical behavior suggests it can strengthen its influence. Similarly, the interplay of spiritual intelligence that demonstrates can strengthen the relationship between ethical content and student ethical behavior.